2011
DOI: 10.1371/journal.pone.0025039
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid Dehydrogenase-1 Is a Novel Regulator of Skin Homeostasis and a Candidate Target for Promoting Tissue Repair

Abstract: 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) catalyzes the interconversion of cortisone and cortisol within the endoplasmic reticulum. 11β-HSD1 is expressed widely, most notably in the liver, adipose tissue, and central nervous system. It has been studied intensely over the last 10 years because its activity is reported to be increased in visceral adipose tissue of obese people. Epidermal keratinocytes and dermal fibroblasts also express 11β-HSD1. However, the function of the enzymatic activity 11β-HSD1 in sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 35 publications
6
78
1
1
Order By: Relevance
“…As cortisol has potent anti-inflammatory effects, the expression level of 11b-HSD1 may influence immune responses (14). It has also been reported that 11b-HSD1 regulates keratinocyte proliferation, but not differentiation (9,10). This knowledge taken together suggests that cholesterol might attenuate the contact hypersensitivity reaction partly via sustained expression of 11b-HSD1 in our mouse models.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…As cortisol has potent anti-inflammatory effects, the expression level of 11b-HSD1 may influence immune responses (14). It has also been reported that 11b-HSD1 regulates keratinocyte proliferation, but not differentiation (9,10). This knowledge taken together suggests that cholesterol might attenuate the contact hypersensitivity reaction partly via sustained expression of 11b-HSD1 in our mouse models.…”
Section: Discussionsupporting
confidence: 54%
“…Quantitative, real-time polymerase chain reaction (RT-PCR) and immunohistochemical staining were performed as previously described (9,10).…”
Section: Experimental Designmentioning
confidence: 99%
“…11␤-HSD1 is widely expressed in human and mouse epidermis and dermis (276,699), but is highest in keratinocytes in the suprabasal area of the epidermis and dermal fibroblasts where it is a reductase (121). Keratinocyte 11␤-HSD1 increases with differentiation (699), parallelling the enzyme's pattern during differentiation of preadipocytes (510).…”
Section: Skinmentioning
confidence: 99%
“…This effect was greatest in Lep ob/ob obese and diabetic mice which have higher cutaneous 11␤-HSD1 expression (although whether or not this reflects increased enzyme in subcutaneous adipose tissue is unclear). This suggests a mechanism by which increased 11␤-HSD1 may contribute to loss of skin elasticity and poorer healing with age (699). The application of inhibitors in skin disease merits examination, especially to promote wound healing, notably in the obese, diabetics, and the elderly.…”
Section: Skinmentioning
confidence: 99%
“…하지만 코 르티솔의 양이 과도하게 증가되면 다양한 질병을 일 으키는 원인이 되기도 한다. 더욱이 피부에서는 11β -HSD1의 발현이 피부 노화와 염증 반응에 관여하며, 피부 항상성 조절에도 영향을 미친다고 보고되었다 [20][21][22][23]. 특히 Itoi 등은 사람 각질형성세포에서 11β -HSD1에 의한 코르티솔 농도 조절이 염증성 사이토 카인의 발현에 영향을 미친다는 결과를 확인함으로써 스트레스에 의한 새로운 피부 염증 메커니즘을 제안 하였다 [20].…”
Section: 결론 및 고찰unclassified